Wystawy sztuki niemieckich towarzystw oraz udział w nich artystów bydgoskich (1878-1912) (Kronika Bydgoska, 2021)
This article describes issues related to development of artistic life in Bydgoszcz in relation to art exhibition, and thus a form representative for organizers, artists and viewers as recipients. The time span is outlined by the following dates, 1878 – establishing of the Bydgoszcz Art Society (Bromberger Kunstverein) and 1912 – the last exhibition of the German Art and Science Society (Deutsche Gesellschaft für Kunst und Wissenschaft). All exhibitions organized by the mentioned societies were reported in chronological order, presenting their history and activity in the scope of exhibition, authors and titles of artworks shown at consecutive art shows, particularly artists representing the Bydgoszcz art community. Providing insight into exhibition related activities of German art societies was aimed at learning about their exhibition concept in Bydgoszcz and presenting activity of local artists. Initially, rather fast growing artistic life in Bydgoszcz under the Prussian rule was interrupted for about ten years at the turn of the 20th century. The defeat of Germany during World War I made that German residents of Bydgoszcz, including artists, left town, and the reviving Polish city of Bydgoszcz had to develop its own art community from scratch.